STEREOTIPE PERAN GENDER BAGI PENDIDIKAN ANAK - Zaduqisti, Esti (MUWAZAH, 2009)
Stereotype concerning gender role has attached on society. Paradigm which views the label differential between female and male characteristics is affected by many factors. Biological, social standpoints, theories of gender psychoanalytical, social cognitive and scheme have concealed influential factors based on its own perspectives. Education based on gender has been one of the programs for government therefore gender bias will be able to be eliminated and the awareness of it will be augmented on many education aspects, for teachers in classes and parents as well. There are many alternative solutions for parents and teachers to be able to encourage learners in having awareness therefore gender bias might be abbreviated.